Mechanism of Transferable Resistance to Chloramphenicol in Haemophilus parainfluenzae - Shaw, William V. (1978)
A clinical isolate of Haemophilus parainfluenzae resistant to chloramphenicol and tetracycline transferred both cam and tet determinants to Escherichia coli K-12 during mixed cultivation on solid media irrespective of the selection employed. The doubly resistant transconjugant was found to contain levels of the enzyme chloramphenicol acetyltransferase (CAT) comparable to those found in R plasmid-bearing chloramphenicol-resistant enteric bacteria. Purification of CAT from the transconjugant was achieved by affinity chromatography, and the electrophoretically homogeneous protein was compared with previously characterized CAT variants specified by R plasmids. Although the CAT associated with cam from H. parainfluenzae was found to be distinct from the three types described previously, its N-terminal peptide amino acid sequence was identical with that determined for a type II CAT. Attempts to demonstrate covalently closed circular deoxyribonucleic acid in the H. parainfluenzae donor and the E. coli transconjugant were unsuccessful. The cam and tet determinants were nontransmissible from E. coli but could be cotransferred following the introduction of a suitable conjugative plasmid.